ANALISIS PENINGKATAN LITERASI PESERTA DIDIK MELALUI PROGRAM KAMPUS MENGAJAR DI UPT SPF SD NEGERI MATTOANGIN 1 - Nur Fadillah, Nut Fadillah; Syukur, Muhammad (DISCOURSE: Indonesian Journal of Social Studies and Education, 2024)
Kampus Mengajar is a program initiated by the Ministry of Education and Culture for students to hone their interests and talents in the field of education, and provide new experiences for students that are not obtained through lectures. The purpose of this study was to determine the improvement of students' literacy skills through the Kampus Mengajar program at UPT SPF SD Negeri Mattoangin 1. The Kampus Mengajar program is to improve the literacy and numeracy skills of students in Indonesia, because the ability to read is important in aspects of life. The research method used is a qualitative method or subject approach. The analysis technique is based on data and field results. The results of this study are an increase in literacy through the Kampus Mengajar program. Through the literacy program designed by teaching campus students at school, we found the impact given through the literacy program at school as well as each stage of the development of improving students' literacy and the efforts made in improving literacy by students of Kampus Mengajar.